Severe acute Q fever pneumonia complicated by presumed persistent localized Q fever endocarditis in a renal transplant recipient: A case report and review of the literature. Issue 1 (16th December 2019) - Budgin, Angela M.; Abidi, Maheen Z.; Bajrovic, Valida; Miller, Matthew A.; Johnson, Steven C.
Abstract: Q fever in solid organ transplant (SOT) recipients is rarely described in the medical literature. We present a case of severe acute Q fever pneumonia that evolved into persistent localized Q fever endocarditis in a renal transplant recipient.